Validation of the Concept of Customary Law in Traditional Lar Sumbawa as a Model for Critical Land Management in Forest Areas - Dianto, Dianto; Gunawan, Jasardi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Land degradation and forest area deterioration in Sumbawa Regency continue to escalate due to unsustainable patterns of natural resource use. This condition requires a new approach that not only relies on state legal instruments but also strengthens social institutions and local wisdom that have long existed within the community. One of the systems that persists is the Lar tradition, a customary law–based mechanism for regulating grazing and land management that ensures a balance between rights, responsibilities, and environmental sustainability. This study aims to validate the concept of customary law within the Sumbawa Lar tradition as a model for addressing critical land in forest areas. The research employs a juridical-sociological approach through field observations, interviews with customary leaders and forestry managers, and qualitative analysis of social practices and customary values that shape the Lar system. The findings indicate that the Lar tradition functions as a living law that embodies regulatory, conservative, and restorative norms in natural resource management. The implementation of this system has proven to enhance community participation and increase the effectiveness of critical land rehabilitation in limited production forest areas. The novelty of this research lies in developing the concept of validating Lar customary law as a community-based model for managing critical land that can be integrated into social forestry policies, thereby strengthening collaboration between customary law and state law in maintaining forest ecosystem sustainability.